Criminal Law Policy In Law Enforcement Of Sim-Swab Crime - Dwi Margono; Jawade Hafidz (Law Development Journal, 2021)
This study aims to examine and analyze criminal law policies in law enforcement of SIM-Swab crimes, obstacles and legal consequences as well as solutions in law enforcement of SIM-Swab crimes. The research method and approach method used in solving the problem is empirical juridical, namely by reviewing the applicable legal provisions and what is happening in reality in society. The results showed that emergence and development of SIM-Swab crimes has a complex background, not only due to unplanned and well-organized economic development, but also other socio-political factors. Therefore, without being supported by policies in other development fields such as social, economic and political fields, the use of criminal law as a means of overcoming SIM-Swab crimes has very limited capabilities. To optimize the function of criminal law in this effort, it is necessary to integrate social policies and criminal politics as well as integration between the use of penal and non-penal means. The enforcement of criminal law against SIM-Swab crimes has not been maximized and the crimes continue to grow. This is inseparable from the various obstacles faced. First, related to the characteristics of SIM-Swab crimes that are difficult to detect. Second, theoretically, criminal law juridical itself provides limitations in law enforcement and there are still various problems, both regarding the substance of the law, law enforcers, conflicts of interest in society, supporting facilities and legal culture in the banking community. So it is necessary to have a number of policies to correct the various deficiencies that exist.